(Micro)Glia as Effectors of Cortical Volume Loss in Schizophrenia. (22nd June 2018) - Mallya, Allyson P; Deutch, Ariel Y
Abstract: Contrary to the notion that neurology but not psychiatry is the domain of disorders evincing structural brain alterations, it is now clear that there are subtle but consistent neuropathological changes in schizophrenia. These range from increases in ventricular size to dystrophic changes in dendritic spines. A decrease in dendritic spine density in the prefrontal cortex (PFC) is among the most replicated of postmortem structural findings in schizophrenia. Examination of the mechanisms that account for the loss of dendritic spines has in large part focused on genes and molecules that regulate neuronal structure. But the simple question of what is the effector of spine loss, ie, where do the lost spines go, is unanswered. Recent data on glial cells suggest that microglia (MG), and perhaps astrocytes, play an important physiological role in synaptic remodeling of neurons during development. Synapses are added to the dendrites of pyramidal cells during the maturation of these neurons; excess synapses are subsequently phagocytosed by MG. In the PFC, this occurs during adolescence, when certain symptoms of schizophrenia emerge. This brief review discusses recent advances in our understanding of MG function and how these non-neuronal cells lead to structural changes in neurons in schizophrenia.